Strengthening the Resilience of Sugihen Tourism Village to Climate Change through Digital Innovation and Green Tourism - Yogi Putra; F Furqan; Mega Hernawati Harefa (CV. Media Digital Publikasi Indonesia, 2026)
The aim of this study was to investigate how resilience, digital innovation, and green tourism can enhance climate change adaptation in Sugihen Tourism Village, North Sumatra. Through a stratified proportional random sampling procedure, 300 respondents representing tourism company owners, local communities, village government, tourism awareness groups, and tourists were surveyed to collect quantitative data. Surveys and interviews were used to collect primary data, while government statistics and relevant publications were used to collect secondary data. Structural Equation Modeling (SEM) using SmartPLS 4 was used for data analysis. The findings revealed that climate change adaptation was positively and significantly influenced by resilience, digital innovation, and green tourism. Furthermore, the relationship between resilience and climate change was significantly mediated by digital innovation and green tourism, indicating that the adoption of sustainable tourism practices and technological solutions is more common in resilient areas. These results imply that combining digital innovation with green tourism tactics can enhance tourism competitiveness, promote sustainable local development, and improve climate resilience at the village level. Policymakers and stakeholders in rural tourism destinations facing climate change issues can benefit from this research's conceptual model, which integrates digital transformation, socio-ecological resilience, and environmentally conscious tourism.